PENGARUH PENGGUNAAN PAYLATER DALAM E-MARKETING TERHADAP PERILAKU PEMBELIAN IMPULSIF MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Rita Natasia Pakpahan; Warneri Warneri; Jumardi Budiman (Universitas Tanjungpura, 2022)
The Indonesian Internet Service Providers Association has conducteda survey internet penetration and internet user behavior in Indonesia2019. The survey results show that Indonesian internet users havereached around 171.17 million. This means that the number ofinternet users is 64.8% of the total population of Indonesia. One thee-marketing innovations by providing PayLater facilities. PayLater isa credit card-like payment method where the app company pays theuser's bill the merchant. The presence of PayLater can be a solutionfor residents to shop when they don't have money. Easy registrationrequirements make people tempted to use it. So there is an allegationthat how to shop using PayLater services can affect product buyingbehavior impulsively. Informants in this study were 32 studentsEconomics Education. This type of research is quantitative whichidentifies the effect of using paylater in e-marketing on students'impulsive buying behavior. The data collection technique used in thisresearch is the questionnaire method. The results the research anddiscussion showed that students Economics Education FKIP Untanhad a good perception of paylater and e-marketing but the use ofpaylater in e-marketing did not significantly affect impulsive buyingbehavior in Economics Education students of FKIP UNTAN.